Remodelling of skeletal tissues bone and structural specialisations in an elasmosaurid (Sauropterygia: Plesiosauroidea) from the Upper Cretaceous of Patagonia, Argentina - Talevi, Marianella (2015)
Elasmosauridae were cosmopolitan Late Cretaceous plesiosaurs with conspicuous morphological diversity. Within this group, vertebral morphology is a criterion for estimating relative age in plesiosaur. On the other hand, the microstructure of plesiosaur bone is considered as indicative of ontogenetic stage. However, knowledge about ontogenetic tissue transformation in different elements of the skeleton is poorly known. Resorption and remodelling of skeletal tissues are required for development and growth, mechanical adaptation, repair and mineral homeostasis of the vertebrate skeleton. This contribution analyses different postcranial elements of a Late Cretaceous elasmosaurid from Patagonia. Characterisation of bone microstructure indicates the presence of compact bone inner organisation in an adult derived plesiosaur from the Cretaceous and that the distribution of bone specialisations depicts conspicuous variations within a single skeleton depending on the skeletal element considered. Bone compactness or degree of remodelling in elasmosaurids is not necessarily correlated with the ontogenetic age of the animal or to costal versus pelagic lifestyles. The available data are still scarce, but we propose a topic of discussion: perhaps the degree of remodelling and compactness also may be related to the activity level and increased mechanical load in different skeletal elements.